The Roles of Supply Chain and Safety Culture on Nuclear Installations Management System: An In-Depth Interview - K.I. Ismara; Fatma Lestari; Sunarto Sunarto (International Journal of Supply Chain Management, 2020)
Abstract-There is inclusion of cultural aspects are necessary by the organization a unified approach is necessary, more specially when elements of the organizational and safety culture plays an important role to achieve the settled goals of an organization inclusive of the safety goals. Study aimed to analyze the relationship between supply chain, zero tolerance, safety’s priority and nuclear management system with mediating effect of teamwork. This prima aim of this paper is to shine the spotlight on the safety culture in nuclear installation system. It also define the importance and need of the safety culture in such a sensitive nature nuclear management to avoid any kind of nuclear disaster. It’s a quantitative study with certain recommendations to evaluate the safety culture importance. This evaluation will conducted not only take prior but also during the installation operations.